Injury mechanisms in fatal Australian quad bike incidents. (18th May 2016) - Mcintosh, A. S.; Patton, D. A.; Rechnitzer, G.; Grzebieta, R.
ABSTRACT: Objectives: The ability to determine risk management controls for quad bike use is confounded by limitations in crash and injury information. The aim of this article is to identify the injury mechanisms, crash characteristics, and contributing factors in fatal quad bike incidents in Australia by activity (recreation and work). Methods: An in-depth case series study was undertaken of 106 Australian quad bike fatalities that had occurred between 2000 and 2013. All case material held by Australian coroners was obtained and reviewed. Results: One hundred and six cases were categorized as occurring during recreation (53) and work (53). Fifty-two of the work cases occurred during farmwork. The mean age for those killed during a work activity was 56 years compared to 27 years for recreational riders. Two children under 16 years died while performing farmwork and 13 children under 16 years during recreational activities. The analyses show a very clear pattern for farmwork-related deaths: quad bike rolls or pitches over (farmworker, 85%; recreational rider, 55%), rider becomes pinned under quad bike (farmworker, 68%; recreational rider, 30%), and death by asphyxia (farmworker, 42%; recreational rider, 11%). In contrast, recreational riders suffered complex impact injuries to the head and chest that occurred when the rider was traveling at speed, lost control, was ejected, and collided with an object in the environment and/or interacted with the moving quad bike. Conclusions: The analyses support the need to improve safe quad bike operation through consideration of the age of the rider, training, helmet use, reducing the propensity of quad bikes to roll, and improving handling so that loss of control events are reduced and to prevent crushing and pinning by the vehicle during and after a rollover crash.